Textual Analysis of Liquidity Risks in the Management Discussions and Analysis Section of 10-K Annual Reports - Beisembayeva, Bela; Procházka, David, 1979 říjen 10.-; Yang, Fan; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2025)
Textual analysis may provide additional information about the company's health. However, the absence of specific word lists complicates matters. Therefore, this master's thesis is focused on comparing the lexicon of companies that face potential liquidity risks and companies that do not. The empirical evidence is based on findings from the Management's Discussion and Analysis section from publicly traded companies that are required to file financial reports with the U.S. Securities and Exchange Commission (SEC). Based on the results, it was confirmed that the lexicons of the two groups differ, and companies with a high percentage of words associated with potential liquidity risks are inclined to have an elevated current ratio.
Vedoucí práce: David Procházka
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: účetnictví a finanční řízení podniku [obor dipl. práce]; diplomové práce; master's theses